A BRIEF HISTORICAL SKETCH - Aziza Sadikovna, Musinova; Oybek Norqulovich, Shomurodov (International Journal of Psychosocial Rehabilitation, 2020)
This article describes the history of the development of minted art on the territory of the former Commonwealth countries. Copper-chased art is one of the ancient arts of mankind. In terms of age, art of decorating metal items in relief is second only to ceramic art. The article talks about the technique of production of metal products from different schools. Examples of works by famous masters of this industry are given. About how they played an important role in everyday life as indicators of social status and wealth. The continuity of traditions, from century to century, has developed in toreutic art specific aesthetic principles and a high standard of artistic performance. More often than not, toreutic items in metal, which were in great demand, served as a source of disseminating new ideas and new methods of artistic expression, thus enriching local tradition with the best achievements in the art of neighboring countries.